Assessment for Education : Standards, Judgement and Moderation - Klenowski, Val, 1952- and Wyatt-Smith, Claire (Los Angeles Sage, 2014)
A guide to assessment for anyone working in curriculum and assessment policy, demonstrating the principles and practice of assessment for improving learning and education.
Include Table and Index
Keywords: Educational tests and measurements -- Education--Evaluation -- Education--Standards